Respostas

A melhor resposta!
2013-07-13T00:29:24-03:00
A) 3A

A= [1 3]   , 3A= [3 9] 
     [2 4]            [6 12]

B) 1/3 (A+B)

(A+B)=  [1 3]  +   [2 -1]  = [3 2]
            [2 4]        [4 0]      [6 4]

1/3(A+B)=  (1/3){ [3 2] } = [1 2/3]
                        { [6 4] }    [2 4/3]

C) 2A-(B+C) = 2*[1 3] -([2 -1]+[0 -6] ) = [2 6] - [2 -7] = [0 13]
                         [2 4]  ([4 0]   [4 2 ])     [4 8]   [8 2]     [12 10]


D)2*(A-C) + 3*(B-A)

2*(A-C)=2*( [1 3] - [ 0 -6] ) = 2* [1  9] = [2 18]
                ( [2 4]   [ 4  2] )        [-2 2]    [-4 4]

3*(B-A)=3*( [2  -1] -  [1 3] ) = 3*([1 -4]) = [3 -12]
                ( [4   0]    [2 4] )       ([2 -4])    [6 -12] 
Como,

2*(A-C) + 3*(B-A) = [2 18] + [3 -12] = [5  6]
                             [-4 4 ]    [6 -12]    [2 -8]
2 5 2